Implementación de un sistema de gestión de la seguridad y salud en el trabajo de acuerdo al Decreto 1072 de 2018 y la Resolución 0312 de 2019 en la empresa Comercializadora de Carnes Premium de Bogotá, D.C. (2020)
This work corresponds to the implementation of the Occupational Health and Safety System (OHSAS) in the Premium Meat Trading Company, applying the guidelines set forth in Decree 1072 of 2015, Resolution 0312 of 2019 and all applicable regulations. To carry out the implementation of the system, the PDVA cycle (plan, do, verify and act ) methodology was used, where an evaluation of the company's conditions was carried out through a diagnosis that evidenced a critical level of 12.5% compliance compared to the minimum standards of OHSAS evidencing that the company required an urgent improvement plan, the legal requirements matrix of the OHSAS was subsequently developed, where the generic and specific standards applicable to the company were established according to its economic activity, and that make up the entire Regulatory Framework of the company.